Middle English texts in transition : a festschrift dedicated to Toshiyuki Takamiya on his 70th birthday - Horobin, Simon; Mooney, Linne; Graham, Timothy (The University of York, 2014)
Fresh contributions to the study of medieval manuscripts, texts, and their creators.
Includes indexes.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism.; Manuscripts, Latin (Medieval and modern); Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Manuscrits latins médiévaux et modernes.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Medieval.; English literature -- Middle English; 1100 - 1500; Geoffrey Chaucer.; History of the Book.; John Gower.; Manuscripts.; Middle English Texts.; Nicholas Love.; Walter Hilton.; William Langland.; Criticism, interpretation, etc.